Effectiveness of a generic vs. specific program training to prevent the short-term detraining on repeated-sprint ability of youth soccer players - Rodriguez-Fernández, A.; Villa, J. G.; Sánchez-Sánchez, J.; Rodriguez-Marroyo, J. A. (The Journal of Strength and Conditioning Research, 2020)
The aim of this study was to analyze the effects of 2 short-term training programs to prevent the negative effect of detraining on repeated-sprint ability (RSA) performance. The study was performed during a 2-week midseason break without official matches. Forty-five youth soccer players (17.7 ± 0.8 years, 175.4 ± 5.5 cm, and 67.2 ± 5.1 kg) were split into 3 groups during the intervention period: inactivity group (IN; N = 16), generic high-intensity training group (GG; N = 15), and specific training group (SG; N = 14). IN was instructed to avoid performing physical activity during the 2-week training intervention. However, GG and SG performed 8 training sessions. GG performed a generic aerobic interval training consisting of 4 repetitions of 4 minutes of exercise at 90-95% of maximal heart rate. SG performed a specific conditioning through small-sided games (4 vs. 4, 4 × 4-minute) and repeated sprints (6 × 30-m). Testing sessions included an RSA test and a Yo-Yo intermittent recovery test level 1 (YYIR1). Repeated-sprint ability performance only improved after the training intervention in SG (~2%, p < 0.01, Eta2p= 0.23-0.25). Both GG and IN declined their performance in post-test (~2%, p < 0.01, Eta2p= 0.19-0.22). No significant effect, group time, was analyzed for YYIR1 performance. This study suggests that only specific training, based on small-sided games and repeated sprints, leads to short-term improvements on RSA performance in youth soccer players.